Removal of Arsenic(III) from Aqueous Solution Using Metal Organic Framework-Graphene Oxide Nanocomposite - Tonoy Chowdhury; Lei Zhang; Junqing Zhang; Srijan Aggarwal (Nanomaterials, 2018)
MIL-53(Al)-graphene oxide (GO) nanocomposites of different GO to MIL-53(Al) mass ratios (1% to 25% GO) were synthesized and tested for removal of arsenite (As(III)), which is a well-known groundwater contaminant. The properties of MIL-53(Al)-GO nanocomposites were characterized using X-ray Diffraction (XRD), Fourier Transform Infrared (FT-IR) Spectroscopy, Brunauer-Emmett-Teller (BET) surface area measurements, and Scanning Electron Microscopy (SEM). Batch experiments were performed on MIL-53(Al)-GO nanocomposites for As(III) adsorption in aqueous solutions to investigate adsorption kinetics and isotherm behavior under varying environmental conditions. The effects of solution pH (2 to 11), initial As(III) concentrations (10⁻110 mg/L), adsorbent dosage (0.2⁻3.0 g/L), and temperature (298⁻318 K) on As(III) adsorption were investigated. MIL-53(Al)-GO nanocomposites showed higher adsorption of As(III) than pristine MIL-53(Al) and GO individually. As (III) removal was optimized at a ratio of 3% GO in the MIL-53(Al)-GO nanocomposite, with an adsorption capacity of 65 mg/g. The adsorption kinetics and isotherms followed pseudo-second-order and Langmuir isotherm models, respectively. Overall, these results suggest that MIL-53(Al)-GO nanocomposite holds a significant promise for use in the remediation of As (III) from groundwater and other aqueous solutions.